Learning and Behavior. - Mazur, James E. (2004)
Keywords: dept.psy; faculty_collection; sabbatical_report

The Roles of Vasopressin and Oxytocin in Memory Processing - McEwen, Barbara B. (Elsevier Academic Press, 2004)
Keywords: Physiological aspects; Research; Memory; Research; Neuropeptides; Research; Oxytocin; Vasopressin; dept.psy; faculty_collection

Multiple Independent Identification Decisions: A Method of Calibrating Eyewitness Identifications - Pryke, S.; Lindsay, R.C.L.; Dysart, J.E.; Dupuis, P. (Journal of Applied Psychology, 2004)
Two experiments (N = 147 and N = 90) explored the use of multiple independent lineups to identify a target seen live. In Experiment 1, simultaneous face, body, and sequential voice lineups were used. In Experiment 2, sequential face, body, voice, and clothing lineups were used. Both studies demonstrated that multiple identifications (by the same witness) from independent lineups of different features are highly diagnostic of suspect guilt (G. L. Wells & R. C. L. Lindsay, 1980). The number of suspect and foil selections from multiple independent lineups provides a powerful method of calibrating the accuracy of eyewitness identification. Implications for use of current methods are discussed.
21 citations (Crossref) [2023-10-31]
Keywords: Decision Making; Humans; Recognition (Psychology); Visual Perception; article; decision making; dept.psy; human; recognition; vision

Varying initial-link and terminal-link durations in concurrent-chains schedules: a comparison of three models. - Mazur, James E (Behavioural Processes, 2004)
In Experiment 1, pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links and fixed delays to food as terminal links. One terminal-link delay was always three times as long as the other. As terminal-link delays increased, response percentages on the key with the shorter terminal link increased according to a curvilinear function. This result supported the predictions of the hyperbolic value-added model and the contextual-choice theory but not delay-reduction theory. In Experiment 2, the terminal links were always delays of 2 s and 12 s, followed by food, and the durations of the initial links varied across conditions. As initial-link durations increased, pigeons' response percentages on the key with the shorter terminal link decreased, but toward an asymptote greater than 50%, indicating a continued preference for the shorter terminal link with very long initial links. This result was more consistent with the predictions of the hyperbolic-value added model than with those of the contextual-choice model or of delay-reduction theory. (C) 2004 Elsevier B.V. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-773-022-282-811 tex.type: [object Object]
Keywords: *Behavior; Animal; *Reinforcement; Psychology; Animals; Behavior; Animal; Columba; Columbidae; Concurrent-chains schedule; Initial links; Key peck; Pigeons; Reinforcement (Psychology); Terminal links; Time Factors; animal experiment; behavioral response; bird; conference paper; controlled study; decision making; dept.psy; experiment; food; intermethod comparison; model; modeling; nonhuman; pigeon; prediction; reinforcement; response time; temporal analysis; theory

Self-esteem, perception of relationships, and emotional distress: A cross-cultural study - Abe, Jo Ann A (Personal Relationships, 2004)
This study examined the relative importance of self-esteem, family cohesion, and support from friends in predicting depressed mood and anxiety in Japanese and American college students. Contrary to expectations, self-esteem was the strongest predictor of emotional distress in both groups of students. Nevertheless, consistent with predictions derived from Markus and Kitayama's theory of self-construals, family cohesion accounted for a significantly larger percentage of the variance in predicting emotional distress in Japan than in the United States. In both countries, the relations between support from friends and the measures of emotional distress were entirely mediated by self-esteem. However, among Japanese students, family cohesion accounted for additional significant variance in predicting the measures of emotional distress, even after controlling for self-esteem.
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-511-906-572-838 tex.type: [object Object]
Keywords: dept.psy

Lexical influences in audiovisual speech perception - Brancazio, Lawrence (Journal of Experimental Psychology: Human Perception and Performance, 2004)
Phoneme identification with audiovisually discrepant stimuli is influenced by information in the visual signal (the McGurk effect). Additionally, lexical status affects identification of auditorily presented phonemes. The present study tested for lexical influences on the McGurk effect. Participants identified phonemes in audiovisually discrepant stimuli in which lexical status of the auditory component and of a visually influenced percept was independently varied. Visually influenced (McGurk) responses were more frequent when they formed a word and when the auditory signal was a nonword (Experiment 1). Lexical effects were larger for slow than for fast responses (Experiment 2), as with auditory speech, and were replicated with stimuli matched on physical properties (Experiment 3). These results are consistent with models in which lexical processing of speech is modality independent.
39 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/108-054-092-602-383 tex.type: [object Object]
Keywords: *Lipreading; *Speech Perception; *Visual Perception; *Vocabulary; Adolescent; Adult; Female; Humans; Lipreading; Male; Phonetics; Reaction Time; Speech Perception; Visual Perception; Vocabulary; adolescent; adult; article; clinical trial; controlled clinical trial; controlled study; dept.psy; female; human; linguistics; lip reading; male; phonetics; randomized controlled trial; reaction time; speech perception; vision

Shame, guilt, and personality judgment - Abe, Jo Ann A (Journal of Research in Personality, 2004)
The purpose of this study was to shed further light on the intrapersonal and interpersonal correlates of shame- and guilt-proneness by examining their relations with self- and peer-ratings of the five-factor model (FFM) of personality. Shame- and guilt-proneness were assessed using a scenario-based and a checklist measure. Consistent with findings from previous research, the self-rating data yielded support for the view that shame-proneness may be associated with more maladaptive patterns than guilt-proneness. However, peer-ratings of personality failed to corroborate these findings. Both scenario-based and checklist measures of shame-proneness were associated with a tendency to underestimate one's Agreeableness relative to peer-ratings. Several possible interpretations of these findings are discussed in light of the extant research on personality judgment. (C) 2003 Elsevier Science (USA). All rights reserved.
43 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-498-536-772-541 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

Gender and identity status differences in late adolescents’ possible selves - Anthis, Kristine; Dunkel, Curt S; Anderson, Brian (Journal of Adolescence, 2004)
The current study examined gender and identity status differences in late adolescents' possible selves. The intent of the study was to clarify conflicts between theory and research on gender differences in identity by investigating the content of participants' possible selves. Participants completed measures of identity and possible selves. The results indicated that there was a relationship between gender and the mean number of both feared and balanced interpersonally themed possible selves. The pattern of results is discussed in terms of prior findings regarding gender differences in both identity and possible selves. Suggestions for future research are also provided. (C) 2003 The Association for Professionals in Services for Adolescents. Published by Elsevier Ltd. All rights reserved.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/125-439-454-273-569 tex.type: [object Object]
Keywords: *Sex Factors; *Social Identification; Adolescent; Adult; Female; Humans; Male; Surveys and Questionnaires; United States; adolescent; adult; article; child behavior; controlled study; coping behavior; dept.psy; ego identity; ethnology; fear; female; gender identity; human; male; personality; race difference; sex difference; social status

Developmental changes in facial expressions of emotions in the strange situation during the second year of life - Izard, Carroll E; Abe, Jo Ann A (Emotion, 2004)
Infants' expressions of discrete emotions were coded during the more stressful episodes (4 through 8) of the Strange Situation at 13 and 18 months. The data showed a significant decrease in full-face expressions (more complex configurations of movements) and a significant increase in component expressions (simpler and more constrained patterns of movements). The authors interpreted this trend as a developmental change toward more regulated and less intense emotions. Consistent with this view, the aggregate index of infants' full-face negative emotion expressions, interpreted as reflecting relatively unregulated intense emotions, correlated significantly with maternal ratings of difficult temperament. The authors discuss alternative interpretations of the findings in terms of changes in reactivity/arousability and the emerging capacity for self-regulation.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-936-730-858-844 tex.type: [object Object]
Keywords: Adult; Affect; Arousal; Facial Expression; Female; Humans; Infant; Social Control; Informal; Temperament; adult; anger; arousal; article; body movement; body posture; child behavior; child development; child parent relation; dept.psy; emotion; face; facial expression; happiness; human; infant; longitudinal study; mother child relation; rating scale; temperament

Therapist variables that predict symptom change in psychotherapy with chronically depressed outpatients. - Vocisano, Carina; Klein, Daniel N; Arnow, Bruce A; Rivera, Caridad; Blalock, Janice A; Rothbaum, Barbara O; Vivian, Dina; Markowitz, John C; Kocsis, James H; Manber, Rachel; Castonguay, Louis G; Rush, A John; et al. (Psychotherapy, 2004)
The present study examines the contribution of psychotherapist variables to change in depressive symptoms in a large clinical trial comparing the efficacy of the cognitive-behavioral analysis system of psychotherapy, the antidepressant nefazodone, and the combination of both in the treatment of chronic depression. Greater change on the Hamilton Rating Scale for Depression (HRSD) was associated with greater emphasis on the therapeutic relationship, lower overall psychotherapy caseload, therapist psychodynamic orientation, and supervisory status. There was no relationship between HRSD change and therapist sex, age, or years of experience.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-228-113-585-108 tex.type: [object Object]
Keywords: Hamilton scale; adult; age; article; behavior therapy; clinical practice; clinical trial; cognitive therapy; controlled clinical trial; controlled study; depression; dept.psy; doctor patient relation; drug efficacy; female; gender; human; major clinical study; male; multicenter study; nefazodone; normal human; outpatient; patient care; patient guidance; physician attitude; prediction; psychodynamics; psychopharmacotherapy; psychotherapist; psychotherapy; randomized controlled trial; symptomatology; workload